Verification of Automobile Aerodynamic Noise Transmitted through Side Window Glass - OKUTSU, Yasuhiko; DOI, Katsunori; YANAGIMOTO, Kazuo; NAKAMURA, Yoshiaki; HAMAMOTO, Naoki (Journal of Environment and Engineering, 2013)
To research the mechanism of automobile aerodynamic noise which transmits to the inside of a cabin, the flow structure and sound field have been investigated by making experimental measurements at the wind tunnel and performing Computational Fluid Dynamics (CFD) based on the Lattice Boltzmann Method (LBM). The noise transmitted at a window glass on the front side is focused in this study. Pressure fluctuations on the side window glass contain both hydrodynamic pressure fluctuations induced by the flow field and acoustic pressure fluctuations propagated from noise sources. It was found by examining the experimental transmission loss that on the side window glass it is close to the random incidence mass law in the high frequency range. To verify the outside sound field, the wave number - frequency spectrum method was applied to computational results in the region behind and outside a sideview mirror. Hydrodynamic and acoustic fluctuations were researched in the wave number - frequency region. This result suggests that the sound field behind the mirror is not a directional sound field but a diffuse sound field.